The impact of Information and Communication Technology (ICT) on learning outcomes in early childhood and primary education: a meta-analysis of moderating factors - Ruijia, Zuo; Wenling, Li; Xuemei, Zhang (Frontiers in Psychology, 2025)
The role of Information and Communication Technology (ICT) in fostering the learning and development of young children and primary school students has become a pivotal focus in contemporary education. This study adopts a meta-analytic approach to systematically synthesize and evaluate findings from 30 recently published studies on the use of ICT in early childhood and primary education. The analysis reveals that ICT has a significant positive effect on student learning, particularly in enhancing language skills (effect size = 0.24) and subject knowledge acquisition (effect size = 0.59). Additionally, the analysis highlights the moderating effects of variables such as intervention duration and application type, emphasizing the need for context-specific implementation strategies. A random-effects model was employed to account for between-study variability, providing robust empirical evidence to inform the design and application of ICT in basic education. The study further recommends that future research prioritize the development of tailored digital resources, the evaluation of long-term impacts, and the exploration of contextual adaptability to fully realize the potential of ICT in enhancing the learning and development of young children and primary school students.